Successful Treatment of Lower Limb Complex Regional Pain Syndrome following Three Weeks of Hyperbaric Oxygen Therapy - Rita Katznelson; Shira C. Segal; Hance Clarke (Pain Research and Management)
Hyperbaric oxygen therapy (HBOT) is a treatment that delivers 100% oxygen at increased atmospheric pressures. The efficacy of HBOT for treating pain has been described in various animal pain models and may have clinical efficacy in the treatment of human chronic pain syndromes. We present our experience with posttraumatic Complex Regional Pain Syndrome (CRPS) type 2 in a patient who underwent 15 sessions of HBOT. A 41-year-old male with one-year history of CRPS of left foot followed by left ankle fracture demonstrated less pain, decreased swelling, less allodynia, and improvement in skin color and range of motion of the lower limb after 3 weeks of HBOT. Patient was back to work for the first time in over a year. HBOT may be considered as a valuable therapeutic tool in the treatment of long-standing CRPS.